The Influence of Brand Image and Brand Awareness on Purchasing Decisions of Mixue Ice Cream & Tea Products in Bandung City on ShopeeFood - NURJAMAD, Moh Aep; PEBRIANTI, Resti Ayu (PT Keberlanjutan Strategis Indonesia, 2025)
This research was conducted on consumers of Mixue Ice Cream & Tea in Bandung City who made purchases through ShopeeFood. The purpose of this study was to determine how much influence Brand Image and Brand Awareness have on Purchasing Decisions, both partially and simultaneously. The research method used in this study is a descriptive and associative method. The sample in this study was 100 respondents. The analysis method used multiple linear regression analysis. Based on the results of the study, it shows that there is a partial and simultaneous influence on the variables of Brand Image and Brand Awareness on Purchasing Decisions. The influence of Brand Image on Purchasing Decisions is 19%, while the influence of Brand Awareness on Purchasing Decisions is 41.5%. The influence of Brand Image and Brand Awareness on Purchasing Decisions is 60.5%.